Multidisciplinary meetings at the emergency department: A conversation-analytic study of decision-making. (December 2019) - Seuren, Lucas M.; Stommel, Wyke; van Asselt, Dieneke; Sir, Özcan; Stommel, Martijn; Schoon, Yvonne
Abstract: Multidisciplinary meetings (MDMs) have become an established part of many medical disciplines. Much research has been done to investigate the conditions under which they work best. This research, however, has been mostly retrospective and has had little consideration for the actual workings of MDMs. The aim of this study was to determine how Multidisciplinary Teams (MDTs) come to a shared decision and thus how they organize MDMs moment by moment. For this purpose we recorded twenty MDMs at the Department of Emergency Medicine (ED) of the Radboud University Medical Center in The Netherlands between November 2017 and June 2018. These meetings, contrary to those discussed in the literature, were scheduled ad-hoc as patients were seen at the ED and were conducted by small MDTs of between three and six participants, always involving a surgeon, a geriatrician, and an emergency physician. Using Conversation Analysis we found that despite the ad hoc nature of these meetings, teams collaboratively developed a structure that was grounded in everyday medical practice and reached a decision in on average slightly over 10 min. First they do a case presentation in which they share the patient's medical history and results of the physical examination and any medical tests. They subsequently agree on a differential diagnosis, and then develop a work plan. Finally, the decision is often formulated to invite confirmation and make it an interactionally shared decision. The benefit of having an MDM was evidenced by discussion of patients' frailty in particular: it was sometimes omitted during the case presentation, but then consistently requested by the geriatrician. And as we show, it was occasionally invoked as a definitive argument for deciding between surgical or conservative treatment. Our analysis suggests that MDMs can have added value in other disciplines where it is feasible to schedule meetings ad hoc. Highlights: Multidisciplinary Teams organize meetings by working towards shared decision making. Order in small-scale multidisciplinary meetings can be constructed in interaction. MDMs are efficient compared to established forms of patient care.